Hubungan Stres Dengan Kejadian Akne Vulgaris Pada Remaja (Studi Literatur) - topang, edward; Soekanto, Ayly; Sugeng, Maria Widijanti; Wulandari, Retno Dwi (Calvaria Medical Journal, 2024)
Background: Acne vulgaris appears because it is triggered by one of the factors being psychological stress or existing acne vulgaris which will get worse. This research aims to determine the relationship between stress and the incidence of acne vulgaris in adolescents. Methods: The research method used is literature study, which is analyzed based on the results of previous research that have been published in scientific journals and other research sources. Result: From this literature study, all 10 journals reviewed (100%) showed a significant relationship which proved to be a correlation between stress levels and the emergence of acne vulgaris in teenagers. Plus, there are other factors that have been found to trigger acne vulgaris. The correlation from this research is related to the level of stress and the emergence of acne vulgaris. Thus, the higher a person experiences a level of stress, the more likely it is that acne vulgaris will appear. Conclusion: Conclusions obtained from research in all journals that provide studies on the relationship between stress levels are proven to be related to the emergence of acne vulgaris that appears in adolescents, and these variables are significantly related.